ANALISIS PENINGKATAN KINERJA PENJUALAN MELALUI SOCO: KEMAMPUAN ADAPTABILITAS DAN KUALITAS KOMUNIKASI (Studi Empirik Shopie Marthin di Kota Ambon) - Sarifudin Sarifudin (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to examine and analyze the effect of SOCO (Service orientation customer orientation) on increasing sales performance at Sophie Paris in Ambon City. Test and analyze the effect of adaptability on increasing sales performance at Sophie Paris in Ambon City. Test and analyze the effect of communication quality on improving sales performance at Sophie Paris in Ambon City. The sample is a portion or representative of the population surveyed totaling 50 respondents or at best more than 100 respondents. For this reason, the sample in this study was 100 people and the purposive sampling method was used as a sampling technique with special consideration so that it was suitable to be sampled. Considerations taken in determining the sample are: (1). Consumer users of Sophie Paris products. (2). Men & women aged 17 years and over. (3). Based in the Ambon city area.The results obtained are SOCO influencing the adaptability of Sophie Martin products in Ambon City. SOCO affects the quality of communication on Sophie Martin products in Ambon City. SOCO influences service performance on Sophie Martin products in Ambon City. Adaptability influences service performance on Sophie Martin Products in Ambon City. The quality of communication influences the service performance of Sophie Martin Products in Ambon City. Keyword: SOCO => Adaptability => Kualitas Komunikasi => Kinerja Penjualan